(untitled) (Research, Society and Development, 2023)
The work in vogue aimed to ascertain the percentage of students who are still illiterate in classes from 2nd to 5th grade of Elementary School in a public school, in Juína-MT. For this, a field survey was carried out at the Ana Néri State School in the aforementioned municipality and state. As a method for data collection, a closed questionnaire with four questions involving teachers from the 2nd to 5th grade of Elementary School at the mentioned institution was used. Content analysis was used for data analysis with the use of tables. The work is also the result of a bibliographical research, which had renowned authors and documents as a theoretical foundation. The research resulted in a significant number of students who have difficulties in reading and writing and understanding and interpreting texts, which leads us to an intervention to be carried out in the future with this school in order to contribute to the development of these students, working on their difficulties and simultaneously seeking to awaken a taste for and interest in reading and writing, making them good readers, and consequently critical and reflective citizens in society.